Study on capture capacity of IgG from human serum of lectin from Canavalia maritima by Lectin - ELISA technique - Phuong Lien, Tran Thi; Chau, Truong Van; Lien, Do Ngoc (Academia Journal of Biology, 2014)
The lectin from Canavalia maritima Aublet seeds (ConM) was purified by Sephadex G - 75 column chromatography. Its purity was assessed by SDS - PAGE in presence of 2 - mecaptoethanol. The SDS - PAGE result show that the purified lectin from Canavalia maritima Aublet comprise three bands of protein which are approximately 33, 23 and 18 kDa. With the aim to seek and use a lectin which is specific antibody from human serum, we investigate the capacity capturing specifically IgG purified from human serum in comparision with the other immunoglobulins as IgA, IgM, IgD, IgE from human serum. The results obtained by using LECTIN - ELISA technique show that the lectin from Canavalia maritima Aublet seeds has a capacity capturing specifically IgG from human serum. We prepared the ConM - Sepharose 4B to purify the IgG from human serum. Again, the result obtained demonstrated the specifity of the Canavalia maritima lectin - IgG interaction.